Localized blade-root IBC for rotor-performance enhancement and vibration reduction - Küfmann, P.; Bartels, R.; Wall, B.G. van der (My University, 2014)
This paper focuses on numerical investigations of the effects of non-harmonic Individual Blade Control (IBC) or Localized Pitch Control (LPC). Different non-harmonic control schemes for the blade-root pitch are presented, optimized for performance enhancement as well as simultaneous vibration reduction and compared to a conventional approach using 2/rev Higher Harmonic Control (HHC). The calculations were performed using the DLR’s comprehensive rotor code S4, simulating two different isolated model rotors at an advance ratio of ?=0.32 with a modified Beddoes inflow model and including rotor-fuselage interaction. In simulations with Bo-105 model rotor blades, LPC was found to perform superior to conventional 2/rev HHC, with reductions in required power of up to -3.62% (-2.26% in power and -57.3% in vibration levels during multi-objective optimization). However, when applied to a more modern rotor blade the margins for power savings as well as vibration reduction were found to be significantly lower.